Influence of emotional intensity and leadership traits on social competency of senior secondary school teachers in Oyo State (2021)
Todays school is often a complex social environment of confrontation, miscommunication, manipulation, hostility, and conflict. So much of what takes place in virtually in all schools is grounded in the interrelationships of students and teachers but it seems that most relationships in our schools have problems. Therefore, this study investigated the influence of emotional intensity and leadership traits on social competency of senior secondary school teachers in Oyo State, Nigeria. Three hypotheses was formulated and tested in the study. The population consists of all senior secondary school teachers from where a sample of six hundred and thirty was purposively and randomly selected. Emotional Intensity Scale (r = 0.83), Leadership Traits Scale (r = 0.81) and Social Competency Scale (r = 0.80) was adapted to collect data. Pearson Moment Product Correlation and Regression was used in the analysis. Result shows that there is significant correlation between emotional intensity and social competency of senior secondary school teachers in Oyo State (r = 0.165, p < 0.05). Equally, a significant correlation exist between leadership traits and social competency (r = 0.116, p < 0.05). Moreover, the predictor variables, emotional intensity and leadership traits are also significant in predicting social competency (F = 13.041; df (2,627); P < 0.05) while the t-value of both ((3 = 0.164, t{627)= 4.226; P < 0.05); (P = 0.093, t(547)= 2.389; P < 0.05) strongly influence social competency of senior secondary school teachers in Oyo State. To cope with emotional demands, teachers require good emotional intensity as well as effective social competence as a leader. It is therefore recommended that school teachers should manage their emotions effectively for learning to take place.